<h3>
Answer: p = 48</h3>
===========================================================
Explanation:
We're told that "p is directly proportional to the square of q", which means that we have the equation
p = k*q^2
for some constant k
Replace p with 12 because we're also told that p = 12.
So we now have this equation
12 = k*q^2
which is the same as
kq^2 = 12
We'll use this later.
-----------------------
Let's go back to the original equation. We'll replace q with 2q to represent the value of q doubling
p = k*q^2
p = k*(2q)^2 ... replace q with 2q
p = k*4q^2
p = 4k*q^2
p = 4*(kq^2)
p = 4(12) ...... replace kq^2 with 12
p = 48
Therefore, if q is doubled, then p = 12 quadruples to p = 48.
Answer:24/3
Step-by-step explanation:
The answer is that she bought 300 packages of paper cups for a party
Answer:
(8-5)*(6+7+(8-6)+(7-5))
Step-by-step explanation:
Answer:
8
Step-by-step explanation:
x=average
(x+x+x+x)/4=average
to increase x by 2 you add 2
x+2=average
(x+2+x+2+x+2+x+2)=4=(4x+8)/4=x+2
you'd have to increase the sum by 8 to make the numbers' averages' go up by 2